A gas-coagulation phase double synergistic low-smoke flame-retardant copolymerized polylactic acid fiber and a preparation method thereof

CN122959877APending Publication Date: 2026-10-23ZHEJIANG UNIV OF TECH TONGXIANG RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611065689.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本发明的目的在于克服现有聚乳酸阻燃纤维阻燃效率低、抑烟效果差、力学衰减严重、基体适配性差、难以规模化生产的技术缺陷,本申请的目的之一在于提供一种气相-凝聚相双协同低烟阻燃共聚聚乳酸纤维,基于L-丙交酯/4-苯基-ε-己内酯共聚聚乳酸基体的结构特性,精准匹配DNPMI磷-氮气相阻燃剂与硅烷改性纳米水滑石凝聚相协效阻燃剂,构建气相淬灭、凝聚阻隔、纳米补强三位一体的改性体系,实现阻燃、抑烟、力学性能的协同提升

Benefits of technology

1、双相协同阻燃机制明确,阻燃效率极高:本发明创新性构建气相-凝聚相双协同阻燃体系,DNPMI气相淬灭与改性水滑石凝聚阻隔双向增效,低添加量下即可实现UL-94 V-0级阻燃,极限氧指数≥30.1%,阻燃性能显著优于传统单一及简单复配改性体系经。KH-560硅烷接枝改性后的纳米水滑石,表面环氧基团可与共聚聚乳酸分子链端羟基、羧基形成共价界面结合,大幅改善无机粉体在有机基体中的分散性,避免纺丝过程粉体团聚造成断丝、喷丝板堵塞;同时改性水滑石高温分解生成镁铝氧化物,催化聚酯交联成致密炭层,协同DNPMI 实现气相 - 凝聚相双重阻燃抑烟效果。。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959877A_ABST
    Figure CN122959877A_ABST
Patent Text Reader

Abstract

The application discloses a kind of gas phase-coagulation phase double synergistic low smoke flame-retardant copolymerized polylactic acid fibers and preparation method thereof, including 94-98 wt% of random copolymer polyester matrix P (LA-co-4-ph-epsilon-CL), 1.0-3.0 wt% of phosphorus-nitrogen flame retardant 3-(6-oxodibenzo[c, e] [1,2] oxygen phosphorus-6-yl)-1-phenyl pyrrolidine-2,5-diketone (DNPMI) and 1.0-3.0 wt% of silane modified nano hydrotalcite, which is prepared by melt blending, melt spinning to form the copolymerized polylactic acid fiber.Based on the structural characteristics of random copolymer polyester matrix P (LA-co-4-ph-epsilon-CL), DNPMI phosphorus-nitrogen gas phase flame retardant and silane modified nano hydrotalcite coagulation phase synergistic flame retardant are accurately matched, a modified system of gas phase quenching, coagulation barrier and nano reinforcement is constructed, and the synergistic improvement of flame retardant, smoke suppression and mechanical property is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional polymer textile materials technology, specifically to a gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber and its preparation method. Background Technology

[0002] Polylactic acid (PLA) is a biodegradable, green polymer material with good biocompatibility, spinnability, and mechanical properties, and is widely used in textile fabrics, protective fabrics, and industrial fibers. However, pure PLA and its copolyester fibers have low limiting oxygen index, are flammable, release large amounts of smoke during combustion, and their molten dripping can easily trigger secondary combustion, which greatly limits their application in high flame-retardant applications such as flame-retardant curtains, industrial protective fabrics, and outdoor flame-retardant fabrics.

[0003] Existing polylactic acid (PLA) flame retardant modification technologies mostly employ single phosphorus-based flame retardants, which have significant technical drawbacks: single phosphorus-based flame retardants rely solely on gas-phase flame retardancy mechanisms, exhibiting weak charring ability and limited smoke suppression effects, and high addition amounts can severely damage fiber mechanical properties; single inorganic nano-flame retardants have limited charring effects and lack gas-phase flame retardancy capabilities, making it difficult to improve flame retardancy ratings; conventional compound systems suffer from low synergistic efficiency, uneven additive dispersion, severe mechanical losses, and high smoke release, failing to simultaneously achieve comprehensive performance of high flame retardancy, low smoke, and high strength.

[0004] Meanwhile, existing flame-retardant modification processes are mostly adapted to ordinary homopolymer polylactic acid, lacking precise flame-retardant modification schemes for the L-lactide / 4-phenyl-ε-caprolactone copolymer system. This fails to fully leverage the structural advantages of the copolymer matrix, and most modification processes have poor compatibility with existing spinning production lines, hindering large-scale production. Based on these shortcomings of existing technologies, there is an urgent need to develop a technology for producing flame-retardant copolymer polylactic acid fibers that combines high flame retardancy, low smoke, excellent mechanical properties, and scalable production. Summary of the Invention

[0005] The purpose of this invention is to overcome the technical defects of existing polylactic acid flame retardant fibers, such as low flame retardant efficiency, poor smoke suppression effect, serious mechanical attenuation, poor matrix compatibility, and difficulty in large-scale production. One of the objectives of this application is to provide a gas-phase-condensed-phase dual synergistic low-smoke flame retardant copolymer polylactic acid fiber. Based on the structural characteristics of L-lactide / 4-phenyl-ε-caprolactone copolymer polylactic acid matrix, DNPMI phosphorus-nitrogen gas phase flame retardant and silane-modified nano-hydrotalcite condensed phase synergistic flame retardant are precisely matched to construct a three-in-one modification system of gas phase quenching, condensation barrier, and nano-reinforcement, so as to achieve synergistic improvement of flame retardancy, smoke suppression, and mechanical properties.

[0006] The second objective of this application is to provide a method for preparing gas-phase-condensed-phase dual synergistic low-smoke flame-retardant copolymer polylactic acid fiber.

[0007] To address the aforementioned technical problems, one of the objectives of this application is achieved through the following technical solution: A gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber comprises 94-98 wt% of random copolyester matrix P (LA-co-4-ph-ε-CL), 1.0-3.0 wt% of phosphorus-nitrogen flame retardant 3-(6-oxodibenzo[c,e][1,2]oxophospha-6-yl)-1-phenylpyrrolidine-2,5-dione (DNPMI), and 1.0-3.0 wt% of silane-modified nano-hydrotalcite, and is prepared by melt blending and melt spinning to form the flame-retardant copolymer polylactic acid fiber.

[0008] The flame-retardant copolymer polylactic acid fiber constructs a gas-phase-condensed-phase dual-synergistic flame-retardant system. In the gas phase, DNPMI flame retardant achieves free radical quenching and smoke suppression. This DNPMI flame retardant exhibits no thermal weight loss within the 200-250 ℃ range and has a thermal decomposition initiation temperature >260 ℃, making it suitable for the melt spinning processing temperature of polylactic acid. The condensed phase is catalyzed by silane-modified nano-hydrotalcite to form carbon, blocking heat and oxygen transfer. The silane-modified nano-hydrotalcite in the gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber decomposes at high temperatures to generate magnesium-aluminum metal oxides, catalyzing the cross-linking and carbonization of the copolymer polyester molecular chains. This forms a continuous, dense, and high-temperature-resistant expanded carbon layer on the fiber surface, effectively blocking the diffusion of external heat and oxygen inwards, while simultaneously preventing the volatilization of combustible small molecules from the matrix, inhibiting matrix thermal degradation and smoke generation. The initial decomposition temperature of the gas-phase-condensed-phase dual synergistic low-smoke flame-retardant copolymer polylactic acid fiber did not decrease significantly compared with pure polylactic acid, and its carbonization ability was enhanced due to the addition of silane-modified hydrotalcite.

[0009] Preferably, the random copolyester matrix P (LA-co-4-ph-ε-CL) comprises L-lactide and 4-phenyl-ε-caprolactone in a monomer mass ratio of 99:1, a catalyst, and a capping agent.

[0010] Preferably, the catalyst is stannous octoate, and the amount added is 0.03%–0.08% of the total mass of the L-lactide and 4-phenyl-ε-caprolactone monomers.

[0011] Preferably, the capping agent is dodecanol, and the amount added is 0.1% of the total mass of the L-lactide and 4-phenyl-ε-caprolactone monomers. (0.001)

[0012] Preferably, the method for preparing the random copolyester matrix P (LA-co-4-ph-ε-CL) includes: A1. Add L-lactide, 4-phenyl-ε-caprolactone, stannous octoate, and dodecanol to a dry high-pressure reactor, seal it, and then evacuate it to -0.095 MPa. Replace the reactor with nitrogen three times to completely remove moisture and oxygen from the system. A2. The high-pressure reactor is heated to 145–155℃, the stirring speed is 80–120 r / min, and the constant temperature polymerization is carried out for 12–16 hours to complete the random ring-opening copolymerization. A3. After polymerization, the temperature is raised to 170℃ and the vacuum degree is -0.098 MPa to remove residual monomers for 3 hours and remove small molecule impurities. A4. The molten material is extruded, water-cooled, and pelletized, and then vacuum-dried at 80°C for 12 h to obtain P (LA-co-4-ph-ε-CL) copolyester particles; the number-average molecular weight of the copolyester particles is 90,000–150,000 g / mol, and the melt index is 5–15 g / 10 min (210°C, 2.16 kg).

[0013] Based on the structural characteristics of L-lactide / 4-phenyl-ε-caprolactone copolymer polylactic acid matrix, this invention precisely matches DNPMI phosphorus-nitrogen gas phase flame retardant with silane-modified nano-hydrotalcite condensed phase synergistic flame retardant to construct a three-in-one modified system of gas phase quenching, condensation barrier, and nano-reinforcement. Through extensive experiments, the optimal raw material ratio and process parameter range were optimized to achieve synergistic improvement in flame retardancy, smoke suppression, and mechanical properties.

[0014] Preferably, the structure of the phosphorus-nitrogen flame retardant 3-(6-oxodibenzo[c,e][1,2]oxophospha-6-yl)-1-phenylpyrrolidine-2,5-dione (DNPMI) is as follows: .

[0015] Preferably, the mass fraction of the phosphorus-nitrogen flame retardant 3-(6-oxodibenzo[c,e][1,2]oxophospha-6-yl)-1-phenylpyrrolidine-2,5-dione (DNPMI) is 1.5-3.0 wt%, preferably 2.5 wt%.

[0016] Preferably, the silane-modified nano-hydrotalcite comprises silane-modified hydrotalcite with a particle size of 40-60 nm and a silane coupling agent with a grafting rate of 8%-12%. The mass fraction of the silane-modified nano-hydrotalcite in the copolymerized polylactic acid fiber is 1.5-3.0 wt%, preferably 1.5-2.5 wt%, and more preferably 2.0 wt%.

[0017] Preferably, the preparation steps of the silane-modified nano-hydrotalcite include: suspension dispersion of silane-modified hydrotalcite powder, silane hydrolysis, isothermal reflux grafting, washing, drying, and sieving; the silane-modified hydrotalcite is magnesium-aluminum type nano-hydrotalcite, and the silane coupling agent is silane coupling agent KH-560; during the preparation of the silane-modified nano-hydrotalcite, the amount of silane coupling agent added is 8%-12% of the mass of the nano-hydrotalcite powder, the reflux modification temperature is 65-75 ℃, and the modification reaction time is 2.5-3.5 h.

[0018] Preferably, the gas-condensed phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber has a limiting oxygen index (LOI) ≥ 31.6%; vertical burning performance reaches UL 94 V-0 level; and tensile strength is 2.4-3.0 cN / dtex, preferably ≥ 2.5 cN / dtex, meeting the mechanical performance requirements of fire safety application scenarios.

[0019] The second objective of this application is achieved through the following technical solution: A method for preparing gas-phase-condensed-phase dual synergistic low-smoke flame-retardant copolymer polylactic acid fiber includes the following steps: S1. Raw material pretreatment: Random copolyester matrix P (LA-co-4-ph-ε-CL), DNPMI flame retardant, and silane-modified nano-hydrotalcite are placed in a vacuum drying oven to dry and remove moisture. S2. Mixing and Batching: Place the dried raw materials in a high-speed mixer according to the specified ratio, and mix for 20-30 minutes at a speed of 200-300 r / min and a temperature of 25-60 ℃ to ensure that DNPMI and silane-modified nano-hydrotalcite are uniformly dispersed in the copolymerized polylactic acid particles. S3. Extrusion and pelletizing: The mixed material is added to a preheated twin-screw extruder for melt blending, extrusion, water cooling, pelletizing, sieving, and vacuum drying at 80 ℃ for 12 h to obtain flame-retardant polylactic acid fiber functional masterbatch. S4. Melt spinning: After drying the flame-retardant composite masterbatch again, the nascent fiber is spun using a melt spinning process. After stretching and heat setting, the gas-phase-condensed-phase dual synergistic low-smoke flame-retardant copolymer polylactic acid fiber is obtained. Preferably, the drying temperature in step S1 is 60-90 ℃ and the drying time is 10-24 h.

[0020] Preferably, the drying temperature in step S1 is 80 ℃ and the drying time is 12 h to remove moisture from the raw materials and avoid defects such as bubbles and broken fibers during the spinning process due to insufficient drying; wherein, DNPMI is a pre-synthesized pure product with a purity ≥ 98%.

[0021] Preferably, the mass ratio of the random copolyester matrix P (LA-co-4-ph-ε-CL), DNPMI flame retardant, and silane-modified nano-hydrotalcite in step S2 is 95.5:2.5:2.0.

[0022] Preferably, the twin-screw extruder in step S3 adopts a gradient heating process, with the following temperatures in each zone: 170-175 ℃ in the feeding section, 175-185 ℃ in the melting section, 185-190 ℃ in the homogenization section, 185-190 ℃ in the die head, and a screw speed of 200-300 r / min.

[0023] Preferably, the screw speed in step S3 is 240-260 r / min, and the temperature gradients of each section are 172 ℃, 180 ℃, 188 ℃, and 188 ℃.

[0024] Preferably, in step S4, the melt spinning temperature of each section of the screw is 180-220 ℃, the spinning speed is 2000-3500 m / min, the draw ratio is 2.5-3.5 times, the heat setting temperature is 60-80 ℃, and the setting time is 5-10 min.

[0025] Preferably, the spinning process parameters in step S4 are as follows: the temperature of each section of the screw is 180 ℃, 185 ℃, 195 ℃, and 210 ℃ respectively; the spinning speed is 2500-3500 m / min; and the draw ratio is 2.8-3.2 times.

[0026] Preferably, the setting temperature in step S4 is 65 ℃ and the setting time is 8 min, which removes internal stress in the fiber, improves the dimensional stability and mechanical properties of the fiber, and finally obtains dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Clear dual-phase synergistic flame retardant mechanism and extremely high flame retardant efficiency: This invention innovatively constructs a gas-phase-condensed-phase dual-synergistic flame retardant system. The dual-effect synergistic effect of DNPMI gas-phase quenching and modified hydrotalcite condensation barrier achieves UL-94 V-0 flame retardancy at low addition levels, with a limiting oxygen index ≥30.1%. Its flame retardant performance is significantly superior to traditional single and simple compound modified systems. The KH-560 silane-grafted modified nano-hydrotalcite has surface epoxy groups that can form covalent interfaces with the terminal hydroxyl and carboxyl groups of the copolymer polylactic acid molecular chain, significantly improving the dispersibility of inorganic powder in the organic matrix and avoiding powder agglomeration during spinning, which can cause fiber breakage and spinneret blockage. Simultaneously, the modified hydrotalcite decomposes at high temperatures to generate magnesium aluminum oxide, catalyzing the crosslinking of polyester into a dense carbon layer, synergistically achieving a dual gas-phase-condensed-phase flame retardant and smoke suppression effect with DNPMI.

[0028] 2. Outstanding low-smoke and environmentally friendly performance: This invention can effectively inhibit the thermal degradation of the matrix and the generation of smoke. The total smoke release is reduced by more than 48% compared with pure copolymer polylactic acid fiber, which greatly reduces the emission of toxic and harmful smoke during combustion, improves the safety of textiles in fire use, and is suitable for high-end flame-retardant and environmentally friendly textile scenarios.

[0029] 3. Excellent and stable mechanical properties. The nano-reinforcing effect of modified nano-hydrotalcite optimizes the microstructure, precisely compensating for the mechanical degradation caused by flame retardant additives. The resulting fiber has a breaking strength ≥2.40 cN / dtex, retaining the excellent textile processing performance of polylactic acid fiber, and can meet the requirements of various fabric weaving and finishing processes.

[0030] 4. High compatibility between matrix and flame retardant system, with good performance and durability: The thermal stability and char-forming ability of phenyl-modified copolymer polylactic acid matrix are better than those of ordinary homopolymer PLA. It forms a structure-function synergy with the two-phase flame retardant system. The fiber is not easy to age and its flame retardant performance does not decline with long-term use, resulting in a longer service life.

[0031] 5. Excellent processing stability, solving the pain point of thermal degradation: The addition of silane-modified hydrotalcite can effectively inhibit the thermal and oxidative degradation of polylactic acid during high-temperature melting and processing, stabilize the melt viscosity, and eliminate production defects such as melt rheological instability, filament breakage, fuzzing, and component pressure fluctuation caused by flame retardant system modification, thereby greatly improving the continuous spinning production capacity and product yield.

[0032] 6. Strong process compatibility and high mass production stability: This invention adopts a fully mature melt processing technology, and the processing temperature is lower than the thermal decomposition temperature of the flame retardant, avoiding the failure of the additives; the optimized gradient extrusion and precise stretching and shaping parameters can effectively eliminate defects such as spinneret blockage and filament breakage, and the spinning and forming is stable, which can be continuously mass-produced. Attached Figure Description

[0033] Figure 1 The limiting oxygen index comparison diagram is shown between the dual synergistic low-smoke flame-retardant copolymer polylactic acid fiber prepared in Example 1 and pure P(LA-co-4-ph-ε-CL) fiber. Figure 2 SEM image of the dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber prepared in Example 1; Figure 3 The TSP curves of the dual synergistic low-smoke flame-retardant copolymer polylactic acid fiber and pure P(LA-co-4-ph-ε-CL) fiber prepared in Example 1 are shown. Detailed Implementation

[0034] The present application will now be further described in conjunction with the accompanying drawings and specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0035] In the description of this application, it should be understood that the terms "upper", "lower", "left", "right", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.

[0036] The terms "first," "second," etc., used in this application are used to distinguish similar objects and not to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that embodiments of this application can be implemented in orders other than those illustrated or described herein, and the objects distinguished by "first," "second," etc., are generally of the same class, without limiting the number of objects; for example, a first object can be one or more. Furthermore, in the specification and claims, "and / or" indicates at least one of the connected objects, and the character " / " generally indicates that the preceding and following objects are in an "or" relationship.

[0037] In the following examples, the number-average molecular weight of P(LA-co-4-ph-ε-CL) used was 106058 g / mol, and the melt index was 10 g / 10 min (210℃, 2.16 kg). The phosphorus-nitrogen flame retardant DNPMI was a pre-synthesized pure product with a purity ≥ 98%. The silane-modified nano-hydrotalcite was prepared in-house, and the preparation process was as follows: 100 g of native magnesium-aluminum hydrotalcite with a particle size of 50 nm was added to 920 g of anhydrous ethanol and 230 g of deionized water to prepare a suspension, which was stirred and dispersed for 30 min. 10 g of KH-560 silane coupling agent was added to glacial acetic acid to adjust the pH to 4.5 and hydrolyzed for 30 min. The hydrolyzed silane was added dropwise to the suspension and refluxed at 70 ℃ for 3 h. The mixture was filtered, washed three times with ethanol, vacuum dried at 80 ℃ for 12 h, and pulverized through a 300-mesh sieve. The final product had a silane grafting rate of 10% and a particle size of 50 nm. Example 1:

[0038] A gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber, comprising: 95.5 wt% P(LA-co-4-ph-ε-CL) copolyester, 2.5 wt% DNPMI flame retardant, and 2.0 wt% silane-modified nano-hydrotalcite; the comonomer mass ratio L-LA:4-ph-ε-CL = 99:1, the number-average molecular weight of the copolyester is 106058 g / mol; the modified nano-hydrotalcite has a particle size of 50 nm and a silane grafting rate of 10%.

[0039] Preparation steps: (1) Raw material pretreatment: All raw materials are placed in an 80 ℃ vacuum drying oven for 12 h to completely remove moisture and avoid yarn breakage during spinning; (2) Melt blending and granulation: After the raw materials are mixed evenly, they are fed into a twin-screw extruder with a temperature gradient of 172 ℃, 180 ℃, 188 ℃ and 188 ℃ respectively, and a screw speed of 250 r / min. The mixture is then water-cooled and pelletized to prepare uniform flame-retardant composite masterbatch. (3) Melt spinning and setting: The masterbatch is dried again at 80 ℃ for 12 h. The temperature of each section of the screw is 180 ℃, 185 ℃, 195 ℃ and 210 ℃ respectively. The spinning speed is 2500-3500 m / min, the draw ratio is 3.0 times, and the heat setting is carried out at 65 ℃ for 8 min to obtain the target flame retardant fiber.

[0040] Performance testing: Limiting oxygen index 32.2%, UL-94 V-0 rating, dripping is significantly suppressed, total smoke emission is reduced by 51% compared to pure copolymer polylactic acid fiber, and breaking strength is 2.7 cN / dtex. Example 2:

[0041] Raw materials: 97 wt% copolyester, 1.5 wt% DNPMI, 1.5 wt% modified nano-hydrotalcite; other parameters and preparation process are the same as in Example 1.

[0042] Performance testing: Limiting oxygen index 31.6%, UL-94 V-0 rating, droplet formation significantly suppressed, total smoke emission reduced by 49%, and tensile strength 2.8 cN / dtex. Example 3:

[0043] Raw materials: 95 wt% copolyester, 2.5 wt% DNPMI, 2.5 wt% modified nano-hydrotalcite; other parameters and preparation process are the same as in Example 1.

[0044] Performance testing: Limiting oxygen index 33.4%, UL-94 V-0 rating, droplet formation significantly suppressed, total smoke emission reduced by 53%, and tensile strength 2.6 cN / dtex. Example 4:

[0045] Raw materials: 94 wt% copolyester, 3.0 wt% DNPMI, 3.0 wt% modified nano-hydrotalcite; the preparation process uses general parameters: drying temperature 80 ℃, drying time 12 h, screw speed 200 r / min, screw section temperatures of 180 ℃, 185 ℃, 190 ℃, 200 ℃ respectively, draw ratio 2.5 times, heat setting temperature 60 ℃, time 10 min.

[0046] Performance testing: Limiting oxygen index 32.0%, UL-94 V-0 rating, droplet formation significantly suppressed, total smoke emission reduced by 48%, and tensile strength 2.4 cN / dtex.

[0047] Comparative Example 1 (Pure Copolyester - Blank Sample) Fibers were prepared from pure P(LA-co-4-ph-ε-CL) copolyester using the same spinning process as in Example 1, without any flame retardant additives. Properties: Limiting oxygen index 21.5%, no flame retardant rating, intense burning, severe melt dripping, excessive smoke generation, breaking strength 2.9 cN / dtex.

[0048] Comparative Example 2 (DNPMI flame retardant added only) Only 2.5 wt% DNPMI flame retardant was added; no silane-modified nano-hydrotalcite was used; the rest of the process was the same as in Example 1. Performance: Limiting oxygen index 32.3%, UL-94 V0 rating, smoke emission reduced by 48%, severe melt dripping, tensile strength 2.5 cN / dtex.

[0049] Comparative Example 3 (with only modified nano-hydrotalcite added) Only 2 wt% silane-modified nano-hydrotalcite was added; DNPMI flame retardant was not included; the remaining processes were the same as in Example 1. Performance: Limiting oxygen index 26.5%, UL-94 rating not specified, smoke release reduced by 18%, extremely poor flame retardant and smoke suppression effects, tensile strength 3.0 cN / dtex. The polylactic acid composite fibers and pure copolyester fibers obtained in Examples 1-4 and Comparative Examples 1-3 were subjected to performance tests. Relevant tests and standards were as follows: Fiber mechanical properties: GB / T 14344 2022 "Test Method for Tensile Properties of Chemical Fiber Filaments"; Fiber flame retardant properties: GB / T 5455 2014 "Textiles - Burning Performance Test - Vertical Method"; The relevant performance test results are shown in Table 1 (fiber specifications: 75D / 48F, FDY). Example 1 2.7 67 32.2 V-0 Significantly inhibits combustion and prevents afterburning. Example 2 2.8 78 31.6 V-0 Significantly inhibits combustion and prevents afterburning. Example 3 2.6 69 33.4 V-0 Significantly inhibits combustion and prevents afterburning. Example 4 2.4 70 32.0 V-0 Significantly inhibits combustion and prevents afterburning. Comparative Example 1 2.9 54 21.5 NR Large amounts of water dripped, and the fire continued to burn. Comparative Example 2 2.5 57 32.3 V-0 It drips in large quantities and does not continue to burn. Comparative Example 3 3.0 60 26.5 NR Large amounts of water dripped, and the fire continued to burn. The above embodiments are merely preferred embodiments of this application and should not be construed as limiting the scope of protection of this application. Any non-substantial changes and substitutions made by those skilled in the art based on this application shall fall within the scope of protection claimed by this application.

Claims

1. A gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber, characterized in that, The flame-retardant copolymer polylactic acid fiber is prepared by melt blending and melt spinning, comprising 94-98 wt% of random copolyester matrix P (LA-co-4-ph-ε-CL), 1.0-3.0 wt% of phosphorus-nitrogen flame retardant 3-(6-oxodibenzo[c,e][1,2]oxophospha-6-yl)-1-phenylpyrrolidine-2,5-dione (DNPMI), and 1.0-3.0 wt% of silane-modified nano-hydrotalcite.

2. The gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber according to claim 1, characterized in that: The random copolyester matrix P (LA-co-4-ph-ε-CL) comprises L-lactide and 4-phenyl-ε-caprolactone in a monomer mass ratio of 99:1, a catalyst, and a capping agent.

3. The gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber according to claim 2, characterized in that: The catalyst is stannous octoate, and the amount added is 0.03%–0.08% of the total mass of the L-lactide and 4-phenyl-ε-caprolactone monomers.

4. The gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber according to claim 2, characterized in that: The capping agent is dodecanol, and the amount added is 0.1% of the total mass of the L-lactide and 4-phenyl-ε-caprolactone monomers. (0.001) 5. A gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber according to any one of claims 2 to 5, characterized in that: The preparation method of the random copolyester matrix P(LA-co-4-ph-ε-CL) includes: A1. Add L-lactide, 4-phenyl-ε-caprolactone, stannous octoate, and dodecanol to a dry high-pressure reactor, seal it, and then evacuate it to -0.095 MPa. Replace the reactor with nitrogen three times to completely remove moisture and oxygen from the system. A2. The high-pressure reactor is heated to 145–155℃, the stirring speed is 80–120 r / min, and the constant temperature polymerization is carried out for 12–16 hours to complete the random ring-opening copolymerization. A3. After polymerization, the temperature is raised to 170℃ and the vacuum degree is -0.098 MPa to remove residual monomers for 3 hours and remove small molecule impurities. A4. The molten material is extruded, water-cooled, and pelletized, then vacuum-dried at 80°C for 12 h to obtain P (LA-co-4-ph-ε-CL) copolyester particles; the number-average molecular weight of the copolyester particles is 90,000–150,000 g / mol, and the melt index is 5–15 g / 10 min.

6. The gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber according to claim 1, characterized in that: The silane-modified nano-hydrotalcite comprises silane-modified hydrotalcite with a particle size of 40-60 nm, a silane coupling agent grafting rate of 8%-12%, and the mass fraction of the silane-modified nano-hydrotalcite in the copolymer polylactic acid fiber is 1.5-3.0 wt%, preferably 1.5-2.5 wt%, and more preferably 2.0 wt%.

7. The gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber according to claim 6, characterized in that: The preparation steps of the silane-modified nano-hydrotalcite include: suspension dispersion of silane-modified hydrotalcite powder, silane hydrolysis, isothermal reflux grafting, washing, drying, and sieving; the silane-modified hydrotalcite is magnesium-aluminum type nano-hydrotalcite, and the silane coupling agent is silane coupling agent KH-560; in the preparation process of the silane-modified nano-hydrotalcite, the amount of silane coupling agent added is 8%-12% of the mass of the nano-hydrotalcite powder, the reflux modification temperature is 65-75 ℃, and the modification reaction time is 2.5-3.5 h.

8. The gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber according to claim 1, characterized in that: The gas-condensed phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber has a limiting oxygen index (LOI) ≥ 31.6%; its vertical burning performance reaches UL 94 V-0 level; and its tensile strength is 2.4-3.0 cN / dtex, preferably ≥ 2.5 cN / dtex, meeting the mechanical performance requirements of fire safety application scenarios.

9. A method for preparing the aforementioned gas-phase-condensed-phase dual-synergistic low-smoke flame-retardant copolymer polylactic acid fiber, characterized in that, Includes the following steps: S1. Raw material pretreatment: Random copolyester matrix P (LA-co-4-ph-ε-CL), DNPMI flame retardant, and silane-modified nano-hydrotalcite are placed in a vacuum drying oven to dry and remove moisture. S2. Mixing and Batching: Place the dried raw materials in a high-speed mixer according to the specified ratio, and mix for 20-30 minutes at a speed of 200-300 r / min and a temperature of 25-60 ℃ to ensure that DNPMI and silane-modified nano-hydrotalcite are uniformly dispersed in the copolymerized polylactic acid particles. S3. Extrusion and pelletizing: The mixed material is added to a preheated twin-screw extruder for melt blending, extrusion, water cooling, pelletizing, sieving, and vacuum drying at 80 ℃ for 12 h to obtain flame-retardant polylactic acid fiber functional masterbatch. S4. Melt spinning: After the flame-retardant composite masterbatch is dried again, the nascent fiber is spun using a melt spinning process. After stretching and heat setting, the gas-phase-condensed-phase dual synergistic low-smoke flame-retardant copolymer polylactic acid fiber is obtained.

10. The preparation method according to claim 9, characterized in that: In step S2, the mass ratio of random copolyester matrix P (LA-co-4-ph-ε-CL), DNPMI flame retardant, and silane-modified nano-hydrotalcite is 95.5:2.5:2.0.